2019
DOI: 10.3399/bjgp19x702737
|View full text |Cite
|
Sign up to set email alerts
|

Using out-of-office blood pressure measurements in established cardiovascular risk scores: a secondary analysis of data from two blood pressure monitoring studies

Abstract: Item Type Article Authors Stevens, S.L.; Stevens, R.J.; de Leeuw, P.; Kroon, A.A.; Greenfield, S.; Mohammed, Mohammed A.; Gill, P.; Verberk, W.J.; McManus, R.J. Citation Stevens SL, Stevens RJ, de Leeuw P et al (2019) Using outof-office blood pressure measurements in established cardiovascular risk scores: implications for practice. British Journal of General Practice. 69(683): e381-e388. Rights AbstractBackground: Blood pressure (BP) measurement is increasingly carried out through home or ambulatory monitorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Nonetheless, our findings were consistent when we limited the sample to whites, and when we limited analyses to those with relapsing remitting MS. We assessed blood pressure based on one measurement but usual blood pressure may be estimated more accurately by averaging several measurements. Nonetheless, 24 hour ambulatory blood pressure monitoring has little effect on the predictive accuracy of the FRS (Bell et al, 2014;Lay--Flurrie et al, 2019). Hyperlipidemia was not used to calculate our primary exposure of interest (FRS) and was assessed based on self-report and medical records review rather than lipid testing.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, our findings were consistent when we limited the sample to whites, and when we limited analyses to those with relapsing remitting MS. We assessed blood pressure based on one measurement but usual blood pressure may be estimated more accurately by averaging several measurements. Nonetheless, 24 hour ambulatory blood pressure monitoring has little effect on the predictive accuracy of the FRS (Bell et al, 2014;Lay--Flurrie et al, 2019). Hyperlipidemia was not used to calculate our primary exposure of interest (FRS) and was assessed based on self-report and medical records review rather than lipid testing.…”
Section: Discussionmentioning
confidence: 99%
“…47 Recently, another study also showed that using BP measurements obtained through ABPM or HBPM instead of OBPM may have little effect on CVD risk estimates obtained from the Framingham, QRISK2 (risk of developing a heart attack or stroke over the next 10 years), or SCORE (Systematic COronary Risk Evaluation) risk equations. 48 Therefore, current cardiovascular risk assessment systems, including China-PAR (Prediction for Atherosclerotic CVD [ASCVD] Risk in China), 49 European SCORE, 50 ASCVD-PCE (Pooled Cohorts Equations) of the USA, 51 the Q risk score (QRISK) model of Great Britain, 52 and the Framingham Risk Score, 53 include only clinic BP in the model. However, all of these cardiovascular risk assessment systems were developed in the general population.…”
Section: Applications For Out-of-office Bp Monitoringmentioning
confidence: 99%
“…Our simulation did not investigate the possibility of discordant results between different types of measurement, such as high office BP and normal ambulatory BP or home BP in people with a true SBP <140 mmHg (‘white-coat hypertension’) or normal office BP and high ambulatory BP or home BP in people with true SBP at least 140 mmHg or abnormal BP response (including ‘masked hypertension’, ‘nocturnal hypertension’ and an exaggerated blood pressure response to exercise), nor the possibility that BP variation itself provides important prognostic information [ 41 ]. However, we note that when using a risk-based approach rather than focusing on blood pressure alone, the addition of out-of-office measurements (including night time BP and measures of variability) [ 42 , 43 ] or indeed repeated office measurements [ 44 , 45 ] appear to have minimal impact on clinical decision-making. Finally, we did not explore psychosocial consequences of over diagnosis and underdiagnosis, clinical consequences of overtreatment and undertreatment and health resource use/cost consequences.…”
Section: Discussionmentioning
confidence: 99%